Preferensi Akad dalam Fatwa DSN MUI: Wakalah bil Ujrah vs Hiwalah bil Ujrah pada Pembiayaan Factoring - Suhaeri (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the contract used in factoring financing based on the fatwa of the National Sharia Council No. 67/DSN-MUI/III/2008, which stipulates the use of a wakalah bil-ujrah contract. The central issue addressed is why the chosen contract is not hiwalah bil-ujrah. This research employs a descriptive qualitative method. The findings indicate that the contract applied in factoring activities is wakalah bil-ujrah rather than hiwalah, as factoring involves not only the transfer of receivables but also the collection and management of credit. Moreover, the model of receivables transfer in factoring is classified as a form of hiwalah deemed invalid (ghayr mashrū‘) by the majority of Islamic scholars (jumhūr ulama).